An overview of manufacturing functionally graded adhesives – Challenges and prospects. Issue 2 (25th January 2021) - Marques, J.B.; Barbosa, A.Q.; da Silva, C.I.; Carbas, R.J.C.; da Silva, L.F.M.
ABSTRACT: Adhesive bonding is a constantly growing and compelling method of joining materials and structures mainly due to its cost-effectiveness, reliability and versatility. Its ability of joining a large range of materials and capability of reducing the stress concentrations in the parts to be joined is preferred, in some situations, over the use of other mechanical joining methods such as riveting and bolting. In recent years, adhesive bonding has become a key technology among the various industrial sectors, namely the automotive industry due to its constant demand for lighter, more resistant and environmentally friendly materials. Therefore, it is of great interest to further develop this kind of bonding, by developing functionally graded adhesive joints. Functionally graded adhesives (FGA) can be defined as tailored adhesives, in which the change in composition and/or microstructure is continuous along a position, allowing a more uniform stress distribution along the bondline. Application-wise, these joints are very promising due to their potential high degree of customization, offering more solutions and options regarding design. This overview aims to assess all the current experimental achievements and manufacturing processes in the field of FGA, as well as the complications and concerns that need to be addressed in order to achieve consistent, reproducible-graded joints that can later be transferred to industrial applications.